2020
DOI: 10.1111/jgs.16726
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Caregivers During COVID‐19

Abstract: The conclusion by Shahid and colleagues may be misleading. 1 They suggest that older patients taking inhibitors of the renin-angiotensin-aldosterone system (RAAS) could be at greater risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection as well as of a worse outcome of COVID-19.Results of available studies have not supported the hypothesis that patients treated with RAAS inhibitors, either angiotensin-converting enzyme (ACE) inhibitors or angiotensin receptor blockers (ARBs), are more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 4 publications
4
42
0
1
Order By: Relevance
“…The consequences of the pandemic on the medical care of patients is another factor to consider 17–23 . Finally, the pandemic has had consequences not only on patients but also on caregivers, as reported previously 24 . Our results showed that the overall mean impact of the pandemic on the PD patient's caregiver was similar to that of the patient.…”
Section: Discussionsupporting
confidence: 82%
“…The consequences of the pandemic on the medical care of patients is another factor to consider 17–23 . Finally, the pandemic has had consequences not only on patients but also on caregivers, as reported previously 24 . Our results showed that the overall mean impact of the pandemic on the PD patient's caregiver was similar to that of the patient.…”
Section: Discussionsupporting
confidence: 82%
“…( Suzuki et al, 2020 ) However, during this COVID-19 pandemic, the availability of caregivers becomes limited which may cause dementia patients unable to follow healthcare and preventive measures therefore making them posed a higher risk of contracting an infection from COVID-19. ( Dang et al, 2020 )…”
Section: Discussionmentioning
confidence: 99%
“…The role of the caregiver has become more important in today's society, shouldering a significant responsibility in healthcare delivery, local communities decision making, care for families and individuals, but also in delivering social protection and care on a long-term basis [3]. Informal caregivers are individuals who deliver care to children and adults with disabilities, mental disorders, those who are chronically ill, as well as older family members and friends with specific needs, who may live within or outside the caregiver's home [4,5]. According to the Organization for Economic Cooperation and Development (OECD) [6], 13% of individuals older than 50 years deliver informal care to at least one person weekly.…”
Section: Introductionmentioning
confidence: 99%